Reaching the nonexistent community: foundations for a philosophy of societal future - Elena Vladimirovna Fell; Alexandra Ivanovna Naletova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The urgency of the discussed issue is caused by the need to care about the future - our own and that of our children. We also care about what happens to those generations of people which will populate this planet hundreds of years from now. The sense of future-orientated societal responsibility is reinforced in media, political rhetoric and social theorising. Philosophers and social theorists offer a variety of approaches that aim to safeguard and promote the welfare of future people, but these approaches are diverse and sometimes conflicting. The aim of the research is to emphasize the attitude towards the future in today's society. The methods used in the study: comparative analysis of philosophical theories of the future; synthesis of the main positions and conclusions regarding the understanding of the category "Future"; classification of human capabilities, and a summary of the main results of the classification. The results: The caring attitude towards future is the outer layer of the relational network that the present community members have with the future community. This attitude takes a form of an agent-centred ethical approach, where the patient of our future-orientated intentionality is absent and unable to initiate a demand on our morality or a response to our actions. Статья посвящена вопросу заботы о будущем настоящих и последующих поколений. Авторами рассматриваются современные теории, затрагивающие этот вопрос: теория справедливости Джона Роллза, теория общественного признания Акселя Хоннета, а также анализируется позиция Амартии Сена и Марты Нюсбаум, касающаяся реализации человеческих возможностей, степень которой выступает как критерий социальной справедливости. Цель исследования - подчеркнуть отношение к будущему в современном обществе. Методы, используемые в исследовании: сравнительный анализ философских теорий будущего; синтез основных положений и выводов, касающихся понимания категории "Будущее". Результаты: Авторы приходят к выводу, что тема заботы о будущем представляет собой лишь внешнюю, видимую оболочку сложных отношений настоящего поколения к будущим поколениям. В основе этих отношений остаются собственно интересы настоящего поколения.